Diversity of bioactive compounds from Tropaeolum tuberosum (mashua) - Vilchez Cáceda, Héctor Alexander (2023)
Introduction: Tropaeolum tuberosum (mashua), is a member of the Tropaeolaceae family, is considered an ecological, millenary crop native in Peru, which began to be consumed in The Andes for having nutritional and medicinal properties. The objective of the present literature review is to highlight the importance of mashua as a source of diverse bioactives and to summarize its pharmacological activities. The method of the present study is a literature review, where original scientific articles on pharmacological activity and bioactive compounds of mashua were searched in the following electronic databases: PubMed, ScienceDirect and Google Scholar, published during the period 2019 to 2023. Result: After the bibliographic search, a total of 22 articles were obtained. It is concluded that despite the fact that mashua is attributed several medicinal uses, there are no studies to date that support the efficacy and safety of its use in a pathology. The information presented in this document will be useful to increase the interest and use in the future of the biological compounds of mashua, as well as to give it a new pharmacological or clinical use, 1234 Carolina Takahashi, Hector Vílchez, Jorge Poemape, Alexander Alvia, Antonella Olortegui thus, becoming useful for the creation of a new drug formulation in the future, or through the application of the bioactive compounds of mashua in combination with existing drugs to optimize the treatment of pathologies such as cancer, anemia, lithiasis, among others.